(untitled) (EAAE Annual Conference Proceedings, 2023)
The New European Bauhaus doesn’t propose just a new way of interpreting health and welfare into a new sustainable productive paradigm but may well determine a deep re-establishment of our way of conceiving and inhabiting the European area. All along the Twentieth Century and at the beginning of the new, cities have been the greatest human aspiration places but resulted in consumption models of natural resources – ground, air, water, vegetation – to the degree of “being human on earth” (Berque A, 1996) reached a critical point. In the same period, countryside has been “forgotten” although it is the place where the human knowledge growing, mostly of the technological one, is certainly more than in the cities (Koolhaas R, 2018).